The Social Roles of Prophets in Early Achaemenid Judah - Blenkinsopp, Joseph (Journal for the study of the Old Testament, 2001)
Determining the social role of prophets in the Neo-Babylonian and Achaemenid periods is obscured by the use of conventional prophetic formulas (e.g. ‘thus says Yahweh’) applied to discourse quite different from previously accepted prophetic forms of speech. Since literacy was restricted to a very small minority, there is also the problem of audience or readership. Something can nevertheless be learned from an examination of how designations or labels other than nābî' are used in this period, including mal'āk, şōpeh (meşappeh) and šōmēr. One development that can be traced is the transition from prophet to preacher, from nābî' to mattîp, leading to the emergence of what can be called ‘ecclesiastical literature’. The possibility that such homiletic language (e.g. in Isa. 40–66) may be grounded in a kind of proto-synagogal context is noted. Finally. the political status of the Jewish ethnos after the loss of national independence created a situation favourable to the emergence of sectarianism, and something of this is also detectable in prophetic texts from the early Achaemenid period.